The Gyrinidae (Coleoptera) fauna of Thailand: Key to tribes and genera, with new records and keys to species of Dineutini and Gyrinini - Suksai, Benjamart; Gustafson, Grey T.; Sites, Robert W.; Sangpradub, Narumon (Zootaxa, 2021)
Eighteen species and four genera of the family Gyrinidae are recorded from Thailand. Seven species, belonging to three genera in the tribes Dineutini and Gyrinini, are here treated in detail. Dineutus sitesi Gustafson, Hájek & Miller, D. spinosus (Fabricius), D. unidentatus Aubé, Porrorhynchus marginatus Laporte and Gyrinus sericeolimbatus Régimbart were already known, whereas D. australis (Fabricius) and Gyrinus smaragdinus Régimbart are recorded for the first time. Diagnoses, distribution maps and keys to tribes, genera, and all species of Dineutus and Gyrinus occurring in Thailand are provided. The fourth genus, Patrus (tribe Orectochilini), has been partly revised in a preceding paper.